Metodologi Pemikiran Fazlur Rahman Dalam Memahami Hadits: Menjembatani Konteks Historis Dan Relevansinya Di Era Kontemporer - Muhammad Umar Ibnu Malik (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
In the current era, traditional and fundamental understanding of hadith may not be enough to answer the challenges of problems in the contemporary era, so in this context a contextual and relevant approach to problems is needed in a holistic and comprehensive manner. This article aims to elaborate and analyze in depth the concepts of understanding hadith initiated by Fazlur Rahman historically, contextually, and their relevance in the contemporary era. This research uses historical methods by collecting book literature, journals, articles, then criticizing all existing literature, and analyzing it to create an article. The research findings show that the socio-historical approach uses a regressive model which includes macro asbabul wurud related to social, psychological, geographical, political, anthropological, historical conditions and matters related to the decline of hadith. Emphasizing the ideal-moral concept, the movement is referred to as a progressive movement with a scheme of taking into account the situation and conditions of the macro and micro context, also determining moral goals from macro and micro responses, as well as adapting moral-social goals to the current context. This phenomenon, which Rahman calls the "Double Movement" thinking methodology, allows the reinterpretation of hadith contextually and dynamically, responding to social and moral challenges in the contemporary era. This emphasizes the importance of understanding hadith that is adaptive to changing times, as well as its contribution to strengthening social cohesion through the values ​​of peace and justice.